Penerapan Model Multinomial Logistik Dalam Memprediksi Intensi Berwirausaha Mahasiswa - Triska Dewi Pramitasari; Ratnaning Tyasasih (Universitas Kadiri, 2020)
The main thing that must be considered by universities today is no longer encouraging students to quickly graduate and get jobs, but how students are able to create jobs. Therefore an effort is needed to increase entrepreneurial intention among students. The purpose of this study is to analyze the use of personal financial management, self-efficacy, parental, entrepreneurship education and e-commerce to predict entrepreneurial intentions. The population in this study were all students of the UNARS Faculty of Economics Management Study Program who had taken Entrepreneurship courses (I and II), which were 211 students in 7th semester. The sampling technique used is simple random sampling, where the determination of the number of samples using the Slovin model. The number of samples is 68 students, which are analyzed using multinomial logistics analysis to find out which of the five independent variables can be used to predict student entrepreneurial intentions. The results of this study concluded that personal financial management, self-efficacy and entrepreneurship education can consistently be used to predict medium and large entrepreneurial intentions. Parental can only be used to predict medium-sized entrepreneurial intentions. While e-commerce can only be used to predict the intention of large-scale entrepreneurship.